Refórmese el art. 40 del Código Penal, respecto de la inimputabilidad por minoría de edad - Campoverde Saltos, Fabián Eduardo (2015)
Adolescence undoubtedly is a stage full of changes and both physical, psychological, physiological modifications and -why not- social, when you consider that more teens are endowed with great access to information why which we are facing a "different kind" of adolescents regarding the age at which it becomes necessary to make a critical study of the importance of this "vulnerable" group within society. This research seeks to internalize about the actions committed by teenagers and their impact on the social and legal environment, taking into account the imputability of children under the age of this group -within insert teenagers-as vital to the research, generally considered to minors, when it is obvious the notable differences between a child and a teenager. In this respect some countries in the region have shown some progress in terms of classifying children according to their age, in establishing age groups in those considered attributable to the minors, considering that if it is some have not reached a psychic maturity completely many of them are in a position to know the existence of rules governing society and the consequences they bring not comply. In the course of this research is vital to make a psychological criminology, victimology, sociological and other studies, since the circumstances surrounding a crime committed by a teenager are provided with a number of components which require no limit to the time to find a solution to this major problem is juvenile delinquency. Is leading the analysis of the types of justice, and the subsequent actions to perpetration of the crime imposed on the offender: "In retributive justice offenses are considered as actions against the state, which is why to repress crime there is no other way bigger prisons, sentences greater number of offenders, longer sentences, social rejection, community exclusion. For restorative justice, however, the offense is the act that harms the victim, and not just a violation of criminal law; the victim has a central place in the process and the success of this measure differently than it does justice conventional manner; that is, does not emphasize punishment was violated as but there repair into account. " This conception and some countries are handling could be an initiative to be considered by our country, seeking not only the punishment of the offender but a reparations if possible, which likewise be involved in rehabilitation offender, to vindicate their actions with action for redress their transgression of the law